Mapping Abiotic Stress-Tolerance Genes in Plants - Wang, Richard R.-C (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents the latest research results on plant genes controlling tolerance to abiotic stresses including heat, cold, drought, salt, nitrogen, metals, irradiation, and exogenous phytohormones. The authors report the expression profiles, function/roles in physiological pathways, and chromosomal locations of tolerance genes. The studies involve cytogenetics, genomics, proteomics, and bioinformatics. The information is critical for food security in an environment experiencing global climate changes. Therefore, this book provides a useful reference to students and professionals in plant sciences encompassing genetics, physiology, chemistry, and breeding.